(untitled) (Salud Medicina e Innovación Journal, 2026)
Postoperative infectious complications continue to represent a significant challenge for health systems, not only because of their clinical and economic impact, but also due to persistent structural inequalities that may amplify risk beyond strictly biomedical factors. The objective of this study was to analyze the association between perioperative markers of social vulnerability and the incidence of postoperative infectious complications, integrating clinical variables and territorial determinants within a multivariate explanatory model. A quantitative, observational, and analytical design was conducted using secondary data from official state reports and national and international health agencies covering the period 2021–2023. Descriptive statistics, multivariate logistic regression, confirmatory factor analysis, structural equation modeling, and spatial autocorrelation analysis were applied. The results revealed a significant risk gradient according to NNIS stratification, with a progressive increase in infection incidence as surgical complexity rose. Additionally, social vulnerability demonstrated an independent structural effect on postoperative infection rates, even after controlling for clinical variables. These findings indicate that postoperative infection is a multifactorial phenomenon in which healthcare processes and socioeconomic determinants interact, requiring comprehensive prevention strategies grounded in epidemiological surveillance, technical standardization, and an equity-oriented approach.